Replantation of an avulsed permanent anterior tooth (Update Dental College Journal, 2015)
This case report describes a case of avulsed left maxillary central incisor tooth which was replanted in the dental office. The tooth was gently rinsed of any debris and placed in normal saline during the examination and preparation of the replantation socket. The tooth was replanted and functionally splinted. The following week the tooth was opened for pulp extirpation and placement of calcium hydroxide. Two weeks later, the root canal was filled with gutta-percha and zinc oxide eugenol sealer, and the access cavity was restored with a bonded composite restoration; the splint was removed. Two year clinical and radiological follow up of the case showed ankylosis and infraocclusion of the replanted toothUpdate Dent. Coll. j: 2015; 5 (1): 30-34